2006
DOI: 10.4049/jimmunol.177.2.1070
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation via CD55 on Human CD4+ T Cells Mediated by CD97

Abstract: Decay-accelerating factor (CD55) is a complement regulatory protein, which is expressed by most cells to protect them from complement-mediated attack. CD55 also binds CD97, an EGF-TM7 receptor constitutively expressed on granulocytes and monocytes and rapidly up-regulated on T and B cells upon activation. Early results suggested that CD55 could further enhance T cell proliferation induced by phorbol ester treatment. The present study demonstrates that coengagement of CD55, using either cross-linking mAbs or it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 40 publications
3
97
1
Order By: Relevance
“…The two molecules shared almost identical EGF-like domains and 50% homology in the stalk and the 7TM regions. As well as functional roles in leukocyte migration, recruitment and activation [18][19][20][21], CD97 is known to be involved in angiogenesis and the migration and invasion of tumor cells [22][23][24]. By analyzing the GPS cleavage of CD97-mFc-fusion protein, we show herein that CD97 and EMR2 have very different GPS cleavage efficiencies.…”
Section: Introductionmentioning
confidence: 84%
“…The two molecules shared almost identical EGF-like domains and 50% homology in the stalk and the 7TM regions. As well as functional roles in leukocyte migration, recruitment and activation [18][19][20][21], CD97 is known to be involved in angiogenesis and the migration and invasion of tumor cells [22][23][24]. By analyzing the GPS cleavage of CD97-mFc-fusion protein, we show herein that CD97 and EMR2 have very different GPS cleavage efficiencies.…”
Section: Introductionmentioning
confidence: 84%
“…Both molecules are early activation antigens and are induced on T lymphocytes by the engagement of T-cell receptor/CD3 complex [20]. Indeed, there were few naïve T cells expressing CD25 and CD69 on the surface (less than 2% cells, data not shown).…”
Section: Lps Activates Cd8 1 T Cells and Induces Perforin And Granzymmentioning
confidence: 90%
“…To further analyse the activating role of LPS on CD8 1 T cells, the purified CD8 1 T cells were cultured with either anti-CD3 with or without LPS or IL-12 in the presence or absence of LPS for 72 h. The activation markers, CD25, the IL-2 receptor a-chain and CD69 (a phosphorylated homodimeric surface protein) were detected by FACS [20]. (Fig.…”
Section: Lps Activates Cd8 1 T Cells and Induces Perforin And Granzymmentioning
confidence: 99%
“…DAF, in addition to those roles seen previously in suppressing T-cell responses in vivo, may also play a role in costimulation. It has been reported that the coengagement of DAF and CD3 results in the proliferation of CD4 T cells, indicating that the role DAF plays in T-cell biology is, at best, multifaceted [139].…”
Section: Complement System In Adaptive Immunity: T-cell Immunitymentioning
confidence: 99%